Machine politics: The cultural science of permissionless systems - Rennie Ellie (Cultural Science)
The survival of permissionless blockchains is typically cast as a cryptoeconomic security problem for mechanism designers to resolve. This essay argues that, long-term, these networks may require something that looks more like a UNESCO protection convention for machine culture than an equation. Ethereum’s machine culture is observable through the formation of a “’we’-group” (Hartley & Potts, 2014, p. 76), which is necessary for the establishment of common knowledge. While entry to the group is permissionless, maintaining membership boundaries demands active contributions from validator nodes. The paper discusses concerns that Ethereum’s consensus may be used for purposes beyond itself, making Ethereum vulnerable to external, non-machine political forces. As this begins to manifest, the need to safeguard Ethereum’s intrinsic machine culture becomes apparent—not merely for the sake of the blockchain but to maintain a stable foundation for emerging digital economies and governance structures.